A simple interface circuit for digital readout of lossy capacitive sensors - Hidalgo-López, José Antonio (Elsevier, 2023)
Direct Interface Circuits (DICs) allow straightforward digital reading from a range of sensors. Their architecture consists of a few passive components that help a digital processor (DP) perform a series of charge and discharge processes that provide time measurements to determine the sensor's resistive, capacitive, or inductive magnitudes. This article presents a new DIC that only requires two resistors for the digital readout of a group of sensors with a wide range of applications, namely lossy capacitive sensors. The DP does not need any analog element in its architecture, and the arithmetic operations involved are simple additions and multiplications. Apart from its simplicity, the new circuit brings significant improvements compared to other DICs proposed in the literature for the same type of sensors. Thus, the systematic errors in the capacitance estimates are only 0.30% for a wider range (100 pF − 95.92 nF), and the measurement time is 34% shorter.
Keywords: Circuitos electrónicos; Circuitos de interfaces; Detectores de proximidad; Lossy capacitive sensor; Sensor interface electronics; Time-based measurement; Direct interface circuits; Sensores capacitivos; Circuitos de interfaz directa; Lectura digital de sensores